Mental Process of Transitivity in The Main Character of Horse Girl Movie: A Systemic Functional Linguistic Approach - Nurjannah, Nurjannah (JURNAL PENDIDIKAN BAHASA, 2024)
The research aims to explain the main character's mental process in the Horse Girl movie using Halliday's theory of Systemic Functional Linguistics. The descriptive qualitative research methodology was employed in this research. The Horse Girl movie served as data source downloaded from Netflix. The utterances of the main character is known as data. The downloading, viewing, reading, identifying (pause, annotate, screenshot), classifying, and encoding material that contains mental processes are all methods used to collect data. The researcher's findings are presented, described, interpreted, and concluded in order to apply data analysis methodologies. Based on the researcher's findings and data analysis, the researcher discovered that the data contained mental processes, they are perception, which came from analyzing the utterance that expressed Sarah's emotions; affection, which came from interpreting Sarah's responses on something; and cognition, which came from interpreting the utterance that highlighted Sarah's thinking and knowledge. The mental process is then dissected in order to create a comprehensive mental process that incorporates both participants which are senser and phenomenon.